Termos de troca, ganhos de comércio e crescimento da renda interna bruta real no Brasil de 1948 a 2014 - Estêv\~ao Kopschitz Xavier Bastos; Pedro Américo de Almeida Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– In this paper, we calculate for Brazil the macroeconomic aggregate called Real Gross Domestic Income (RGDI) and trading gains resulting from terms of trade changes, from 1948 to 2014. RGDI equals Real Gross Domestic Product (RGDP) plus trading gains, thus incorporating terms of trade change effects that are not captured by GDP. The international conventions highly recommend that RGDI be an integral part of the System of national Accounts, but it is not calculated in Brazil since 1990 (there are official data for the period 1970-1989). The difference between this two concepts is relevant for the analysis of periods in which there are significant variations in terms of trade.
Keywords: E01; C43; O11; 330; terms of trade; trading gains; real gross domestic income